PENGARUH AUDIT TENURE, UKURAN PERUSAHAAN, DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ45 BURSA EFEK INDONESIA - Annisa Sekar Irsa Fajrina; Julaika Putri Rohkhayatim (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
In this study, we explore the effects of audit tenure, firm size, and public accounting firm size on audit quality of companies which are consistently listed in LQ45 index during August 2018 until January 2019 period. Sample of this research is the financial statement of the stated companies for 2015-2018 period. This research is conducted with quantitative approach using data panel regression analysis. The results indicate that 1) Audit tenure has negative significant effect and 2) Public accounting firm size has positive significant effect on audit quality. Meanwhile 2) Firm size doesn’t have significant effect on audit quality.